Retraction of ‘Enhancing the yield of antitubercular compounds from fenugreek [Trigonella foenum-graecum (Methi)] seeds using response surface methodology' (Journal of Applied Pharmaceutical Science, 2023)
The article titled ‘Enhancing the yield of antitubercular compounds from fenugreek [Trigonella foenum-graecum (Methi)] seeds using response surface methodology’ was published in the Journal of Applied Pharmaceutical Science, Volume 12, Issue 11, pp. 061-070, has been retracted from the Journal of Applied Pharmaceutical Science.The journal received an anonymous complaint that one of the reviewers who took part in the peer review of this article has a direct relationship with the first author. The complainant also provided the name of that reviewer. We investigated the complaint and found that the article was peer-reviewed by four different reviewers, and one of the reviewers who participated in the process is the same person mentioned by the complainant.As per the journal’s policies, the authors and reviewers must disclose any potential conflicts of interest. In spite of having a direct relationship, neither the author nor the reviewer has disclosed any conflicts of interest. In view of the above, it is evident that there is a violation of the journal’s conflict of interest policies and a possibility of manipulation of peer review. Therefore, we retract this article from the literature according to the guidelines of the Committee on Publication Ethics (Wager et al., 2009; COPE, 2019).It is important to note that the first author (Arpita Batta) informed the journal that the other authors listed in the article were unaware of the relationship between the first author and the reviewer, and “only the first author is responsible for the misconduct.”Read the related article: http://dx.doi.org/10.7324/JAPS.2022.121107